Prognostic Value and Correlation With Tumor Immune Infiltration of a Novel Metabolism-Related Gene Signature in Pancreatic Cancer - Chen, Hui; Zu, Fuqiang; Zeng, Taofei; Chen, Ziang; Wei, Jinhong; Liu, Peng; Li, Zeyu; Zhou, Lei; Wang, Huaitao; Tan, Hao; Tan, Xiaodong (Frontiers in Oncology, 2022)
Background: Energy metabolism has been considered as one of the novel features of neoplasms. This study aimed to establish the prognostic signature for pancreatic cancer (PC) on the basis of metabolism-related genes (MRGs). Methods: We obtained MRGs from the Molecular Signatures Database (MSigDB) and gene sequence data in the Cancer Genome Atlas (TCGA) databases. Then, differentially expressed MRGs (DE-MRGs) were identified utilizing the R software. We built the prognostic model via multivariate Cox regression. Moreover, external validation of the prognostic signature was also performed. Nomogram was created for predicting the overall survival (OS). Next, this study analyzed the prognostic value, clinical relationship, and metabolism-related signaling pathways of the prognostic signature. The role in tumor infiltration was further evaluated. Eventually, the expression level of the three MRGs along with the function of NT5E were validated. Results: Twenty-two MRGs were chosen, eight of which were identified to be most significantly correlated with the prognosis of PC. Meanwhile, a 3-MRG prognostic signature was established and we verified this prognostic model in the GSE57495 dataset. What’s more, the nomogram was used to predict 1/2/3-year OS of PC patients. In addition, the immune cell infiltrating and expression of immune checkpoint were significantly influenced by the risk score. Finally, three MRGs were highly expressed in PC cell lines and NT5E was associated with the proliferation and migration ability of PC. Conclusion: To sum up, the study established and validated a 3-MRG prognostic signature for PC, and the signature could be utilized to predict the prognosis and assist the individualized clinical management of patients with PC.